The handbook of journalism studies - Wahl-Jorgensen, Karin; Hanitzsch, Thomas 1969- (International Communication Association (ICA) handbook series, 2019)
This second edition of The Handbook of Journalism Studies explores the current state of research in journalism studies and sets an agenda for future development of the field in an international context. The volume is structured around theoretical and empirical approaches to journalism research and covers scholarship on news production; news content; journalism and society; journalism and culture; and journalism studies in a global context. As journalism studies has become richer and more diverse as a field of studies, the second edition reflects both the growing diversity of the field, and the ways in which journalism itself has undergone rapid change in recent years."--